Effect of Nitrogen Addition on Selection of Germination Trait in an Alpine Meadow on the Tibet Plateau - Liu, Kun; Liu, Yang; Zhang, Zhilong; Zhang, Shiting; Baskin, Carol C.; Baskin, Jerry M.; Liang, Ting; Bu, Haiyan; Li, Shuxia; Zhang, Tingting; Cui, Xianliang; Xiao, Sa (Frontiers in Plant Science, 2021)
Seed germination requirements may determine the kinds of habitat in which plants can survive. We tested the hypothesis that nitrogen (N) addition can change seed germination trait-environmental filter interactions and ultimately redistribute seed germination traits in alpine meadows. We determined the role of N addition on germination trait selection in an alpine meadow after N addition by combining a 3-year N addition experiment in an alpine meadow and laboratory germination experiments. At the species level, germination percentage, germination rate (speed) and breadth of temperature niche for germination (BTN) were positively related to survival of a species in the fertilized community. In addition, community-weighted means of germination percentage, germination rate, germination response to alternating temperature and BTN increased. However, germination response to wet-cold storage (cold stratification) and functional richness of germination traits was lower in alpine meadows with high-nitrogen addition than in those with no, low and medium N addition. Thus, N addition had a significant influence on environmental filter-germination trait interactions and generated a different set of germination traits in the alpine meadow. Further, the effect of N addition on germination trait selection by environmental filters was amount-dependent. Low and medium levels of N addition had less effect on redistribution of germination traits than the high level.